Perencanaan dan Manajemen Komunikasi dalam Membangun Citra Pelayanan Jasa Outsourcing - Abdul Kholik (Communicology: Jurnal Ilmu Komunikasi, 2020)
Communication aims to obtain common ground between the actors of communication. Interactions that occur between outsourcing employees and clients certainly contain quite complex communication phenomena. Clients certainly expect excellent service from outsourcing employees. The general problem formulation in this research is to examine how far the influence of communication planning and management can influence the image of outsourcing services. The theory is based on the Management by Objective Theory pioneered by Peter Drucker. The principle behind Management by Objective (MBO) is to ensure that every employee has a clear understanding of the goals or objectives of the organization, just as they understand their roles and responsibilities in achieving those goals. The results of research carried out produce that there is a significant influence related to the influence of planning and communication management on the image of outsourcing services. The mean on the effect of communication planning is slightly higher with a range of 0.1 compared to communication management. But both of them have almost the same mean values ​​of 3.84 and 3.74. Keywords: Communication, Management by Objective, Outsourcing, Brand Image